Gender of Authobiographical “Self”. The Case of Renáta Tyršová - Filipowicz, Marcin (Poznańskie Studia Slawistyczne, 2016)
The aim of this paper, is to try to use feminist and gender theories to read Slavic cultural material, as well as to complete the picture of diversity of Slavic gender orders. For this purpose, the paper focuses on biographies written by Renáta Tyršová devoted to her father and husband. The analysis of this case requires using the feminist criticism of autobiography theory, which is hardly theoretically absorbed within Slavistics. Article seeks to explore the complexities of the relationship between female individual autobiographical “self”, structure of female gender in the bourgeois society of the 19th century, and finally collective idea of nationalism.